Perspektif Multikultur, Kasus Film 3 Hati 2 Dunia 1 Cinta - Damayanti, Maria Nala (Nirmana, 2011)
Multicultural issues in Indonesia is a new discourse in a culture that is important in connection with a lot of racial conflicts that occurred lately. Film as an audio visual media has a major role in campaigning for the idea. Therefore, analyzing the film with a multicultural perspective will be a separate view that may be developed in relation to its role in this culture. This article reviews '3 Hearts 2 Worlds 1 Love’ a movie which was launched in 2010. Through the analysis of cinema studies, the theoretical approach of multiculturalism, open bids for the audience to take part in the interpretation. In particular the interpretation of cultural practice that is reflected through the film’s narrative.